2015
DOI: 10.1037/a0039478
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of children’s behavioral engagement in late elementary school: Both teachers and peers matter.

Abstract: The present longitudinal study examined how relationships with teachers and peers jointly shape the development of children's behavioral engagement in late elementary school. A sample of 586 children (46% boys; Mage = 9.26 years at Wave 1) was followed throughout Grades 4, 5, and 6. A multidimensional approach was adopted, distinguishing support and conflict as teacher-child relationship dimensions, and acceptance and popularity as peer relationship dimensions. Additive, moderation, and mediation models were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 94 publications
4
44
0
12
Order By: Relevance
“…These results confirm the findings of other studies reporting that peer relationships and the student-teacher relationship are correlated, but are two unique aspects of students' social integration at school (e.g. De Laet et al, 2015;Furrer & Skinner, 2003;Virtanen et al, 2014). In contrast, the student-teacher relationship and relationships with peers seem to be less important for students' truant behavior and neither of them leads to a lower or higher truancy rate.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results confirm the findings of other studies reporting that peer relationships and the student-teacher relationship are correlated, but are two unique aspects of students' social integration at school (e.g. De Laet et al, 2015;Furrer & Skinner, 2003;Virtanen et al, 2014). In contrast, the student-teacher relationship and relationships with peers seem to be less important for students' truant behavior and neither of them leads to a lower or higher truancy rate.…”
Section: Discussionsupporting
confidence: 88%
“…In a number of studies the quality of students' relationships in school has been recognized as one of the prominent factors influencing students' school engagement (e.g. Birch & Ladd, 1997;De Laet et al, 2015;Makarova & Herzog, 2013;Wang & Eccles, 2013), and school-based supportive relationships were shown to have 'a key influence on academic engagement' (Suárez-Orozco, Pimentel, & Martin, 2009, p. 730).…”
Section: Who Is At Risk Of Low School Engagement?mentioning
confidence: 99%
See 1 more Smart Citation
“…The ages of 9 to 12 years are a key period for the development of relational aggression as children's goals of popularity and social dominance peak (De Laet et al 2015). Vaillancourt and Hymel (2006) comment that the term dominance is traditionally applied to people who manipulate the behavior of others; this relates to social power.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has documented that being accepted by the peer group offers many advantages for children's development, not only for their psychosocial development and mental health, but also for their academic success (Gifford‐Smith & Brownell, ; Wentzel & Muenks, ). Longitudinal research has shown that children who are accepted by their peers at school tend to feel more emotionally engaged in school and display higher levels of behavioral school engagement over time (e.g., De Laet et al., ; Weyns, Colpin, De Laet, Engels, & Verschueren, ). These findings are consistent with the assumption that social acceptance fulfills children's need for relatedness, which helps fostering their engagement and achievement (e.g., Wentzel & Muenks, ).…”
Section: Introductionmentioning
confidence: 99%